2010
DOI: 10.1159/000301714
|View full text |Cite
|
Sign up to set email alerts
|

Do ‘Sleepy’ and ‘Tired’ Go Together? Rasch Analysis of the Relationships between Sleepiness, Fatigue and Nonrestorative Sleep Complaints in a Nonclinical Population Sample

Abstract: Objective: The lack of distinction in the clinical use of terms like fatigue and sleepiness is an important issue. While both fatigue and sleepiness can potentially be associated with nonrestorative sleep (NRS) complaints, their relationships are still poorly described. We propose to use Rasch analysis-based methods to study the interrelations of fatigue, sleepiness and NRS. Methods: 150 subjects (mean age = 39.3 years, range = 18–65) from a community sample underwent a structured computer-assisted web intervi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 58 publications
1
34
0
Order By: Relevance
“…It has been used in many studies investigating fatigue in several chronic conditions and in general population samples [43,44]. It is a 9-item, 7-point Likert type scale ranging from “completely disagree” (=1) to “completely agree” (=7).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been used in many studies investigating fatigue in several chronic conditions and in general population samples [43,44]. It is a 9-item, 7-point Likert type scale ranging from “completely disagree” (=1) to “completely agree” (=7).…”
Section: Methodsmentioning
confidence: 99%
“…Scores are usually reported as “mean scores” (ranging from 1 to 7) obtained by dividing the total score (ranging from 7 to 63) by 9. The most often proposed cut-off point on mean scores has firstly been 4 [45] and more recently 5 [43,44]. …”
Section: Methodsmentioning
confidence: 99%
“…As reported by Neu et al 27 fatigue and sleepiness are two different phenomena. According to the same authors, these were used synonymously mainly in the studies, in which only one of these dimensions was studied.…”
Section: Discussionmentioning
confidence: 78%
“…Previous studies have suggested that fatigue and sleepiness are two independent concepts (Shekleton et al, 2010). In both clinical and non-clinical populations, the association between fatigue and sleepiness was found to be weak (Anderson et al, 2003;Hossain et al, 2005;Neu et al, 2010Neu et al, , 2008. For example, in a study of 283 sleep-disordered patients, the Pearson's correlation between fatigue and sleepiness was 0.18.…”
Section: Discussionmentioning
confidence: 99%